Characterization of Polymer Degrading Lipases, LIP1 and LIP2 From Pseudomonas chlororaphis PA23 - Mohanan, Nisha; Wong, Chun Hin; Budisa, Nediljko; Levin, David B. (Frontiers in Bioengineering and Biotechnology, 2022)
The outstanding metabolic and bioprotective properties of the bacterial genus Pseudomonas make these species a potentially interesting source for the search of hydrolytic activities that could be useful for the degradation of plastics. We identified two genes encoding the intracellular lipases, LIP1 and LIP2, of the bacterium Pseudomonas chlororaphis PA23 and subsequently performed cloning and expression in Escherichia coli. The lip1 gene has an open reading frame of 828 bp and encodes a protein of 29.7 kDa whereas the lip2 consists of 834 bp and has a protein of 30.2 kDa. Although secondary structure analyses of LIP1 and LIP2 indicate a dominant α/β-hydrolase-fold, the two proteins differ widely in their amino acid sequences (15.39% identity), substrate specificities, and hydrolysis rates. Homology modeling indicate the catalytic serine in both enzymes located in a GXSXG sequence motif (lipase box). However, LIP1 has a catalytic triad of Ser152-His253-Glu221 with a GGX-type oxyanion pocket, whereas LIP2 has Ser138-His249-Asp221 in its active site and a GX-type of oxyanion hole residues. However, LIP1 has a catalytic triad of Ser152-His253-Glu221 with an oxyanion pocket of GGX-type, whereas LIP2 has Ser138-His249-Asp221 in its active site and a GX-type of oxyanion hole residues. Our three-dimensional models of LIP1 and LIP2 complexed with a 3-hydroxyoctanoate dimer revealed the core α/β hydrolase-type domain with an exposed substrate binding pocket in LIP1 and an active-site capped with a closing lid domain in LIP2. The recombinant LIP1 was optimally active at 45 °C and pH 9.0, and the activity improved in the presence of Ca2+. LIP2 exhibited maximum activity at 40 °C and pH 8.0, and was unaffected by Ca2+. Despite different properties, the enzymes exhibited broad substrate specificity and were able to hydrolyze both short chain length and medium chain length polyhydroxyalkanoates (PHAs), polylactic acid (PLA), and para-nitrophenyl (pNP) alkanoates. Gel Permeation Chromatography (GPC) analysis showed a decrease in the molecular weight of the polymers after incubation with LIP1 and LIP2. The enzymes also manifested some polymer-degrading activity on petroleum-based polymers such as poly(ε-caprolactone) (PCL) and polyethylene succinate (PES), suggesting that these enzymes could be useful for biodegradation of synthetic polyester plastics.